(untitled) (Pakistan Journal of Kidney Diseases, 2021)
Antineutrophil cytoplasmic antibody (ANCA) associated vasculitis limited to the kidney is characterized by necrotizing glomerulonephritis with little or no deposition of immunoreactants (IgG, IgM, IgA, and complement components). We present here a case with renal limited vasculitis and discuss the literature.